Three cases of congenital self‐healing Langerhans cell histiocytosis with BRAF‐V600E mutation. Issue 1 (16th February 2022) - Ramírez‐Lluch, Mar; Colmenero, Isabel; Suárez, José; Carrión‐Marrero, Saulo; Rodríguez‐Fuertes, Francisco; Mateos‐Mayo, Ana; Hernández‐Martín, Ángela; Torrelo, Antonio
Abstract: Congenital self‐healing Langerhans cell histiocytosis (CSHLCH) is a rare variant of Langerhans cell histiocytosis characterised by the presence of skin lesions in the neonate and spontaneous self‐healing after a variable period of time. We report three cases of CSHLCH with BRAF‐V600E mutation and high Ki‐67 proliferative activity.